MOTIVATION TO WORK IN ONLINE FORMAT AS A COMPONENT OF PROFESSIONAL TRAINING AT THE GLOBAL AND NATIONAL DIMENSIONS - Suprun, Daria (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The question of improvement of the motivation of specialists in the field of special and inclusive education to work in online format according to European experiences and practiceshas been raised. The values of online education in the global and national dimensions have been delighted. An analytical review of research’s results has been conducted.